A promptly approach from monosaccharides of biomass to oligosaccharides via sharp-quenching thermo conversion (SQTC). (1st June 2018) - Liu, Xiao; Wei, Weiqi; Wu, Shubin; Lei, Ming; Liu, Ying
Highlights: Preparation of oligosaccharides from monosaccharides was first realized in this study. Using SQTC, the COS/XOS could be obtained within few seconds without introduce any chemical reagent. About 50% COS/XOS yields could be acquired via this environmentally friendly preparation process. The component and structure of produced COS and XOS were thoroughly studied by various technologies. Abstract: In this study, a novel and facile approach of conversion monosaccharides (glucose and xylose) to oligosaccharides (Cello-oligosaccharides and Xylo-oligosaccharides) was demonstrated. The approach did not introduce any chemical reagent and the preparation process could be environmentally friendly. Identification and quantification by ion chromatography (IC) and high performance liquid chromatography (HPLC) showed that the yields of COS and XOS reached to 44.62% (38 s) and 47.09% (30 s) respectively at 500 °C reaction temperature coupled with sharp-quenching method. Structural characterization indicated that such oligosaccharides showed a degree of polymerization (DP) with 2–6, and the units mainly linked by β-(1 → 4)-glycosidic bond.